Facing the Challenges Together: A Collaborative Approach to Understanding Contemporary Government Library and Information Services. Issue 3 (3rd July 2018) - Hallam, Gillian; Sibthorpe, Julie
ABSTRACT: The Commonwealth Government Agency Libraries Review was commissioned by the Executive Committee of the Australian Government Library and Information Network (AGLIN). The review sought to identify how government libraries might best meet the needs of Commonwealth employees by delivering efficient, cost-effective and equitable information services. While a primarily quantitative survey was used in Stage 1 to collect detailed data about individual agency libraries, this article focuses on the qualitative data gathered in a series of focus groups. Library and information professionals discussed the valuable aspects of their work, as well as identifying the range of issues and challenges they faced. In Stage 2, interviews with senior executives and policy managers validated the findings, with the complex mix of positive and negative factors associated with the roles played by librarians acknowledged. The research highlights the urgent imperative for librarians to take advantage of the changing government information environment to reposition their roles. Initiative, leadership and strategic vision are required to ensure that their professional skills are recognised. The project activities themselves demonstrate how collaboration has the potential to develop and support a culture of research into practice in the field of library science.